Probiotic L. gasseri strain (LG21) for the upper gastrointestinal tract acting through improvement of indigenous microbiota. Issue 1 (12th August 2019) - Koga, Yasuhiro; Ohtsu, Toshihiro; Kimura, Katsunori; Asami, Yukio
Abstract : Objective: To describe probiotics including a Lactobacillus gasseri strain LG21 used for the upper gastrointestinal tract, which are considered to act through improvement of indigenous microbiota inhabiting there. Background and design: Because the early definition of probiotics emphasized their effects on improving the intestinal microbial ecology, their effects on the intestinal tract and its immunity have been considered common general benefits associated with probiotics. This conclusion was also based on a body of successful clinical trials whose endpoints were the prevention or treatment of intestinal diseases. In contrast to intestinal microbiota, our understanding of the role of gastric microbiota in human health and physiology remains poor, as the bacterial load in the stomach is considered too small to exert a significant effect due to the highly acidic environment of the human stomach. Therefore, the intervention using probiotics in the stomach is still limited at present.Results:In this article using representative 38 quoted articles, we first describe the gastric microbiota, as the indigenous microbiota in the stomach is thought to be significantly involved in the pathophysiology of this organ, since probiotics exert their beneficial effects through improving the resident microbiota. We then review the present status and future prospects of probiotics for the treatment of upper gastrointestinal diseases by quoting representative published articles, including our basic and clinical data. Conclusions: Probiotics have been demonstrated to suppress Helicobacter pylori in the stomach, and are also expected to improve functional dyspepsia through the correction of dysbiotic gastric microbiota.